1999
DOI: 10.1007/bf02494803
|View full text |Cite
|
Sign up to set email alerts
|

Electrophilic 1,3-C→N− and-N→C− migrations in saturated systems

Abstract: A new type of intramolecular electrophilic rearrangements involving the shift of COOA}k groups from carbon to an N-anionic center is considered. Carbanionic species with COOAIk groups at anionic centers containing no acidic hydrogen react unusually with atkyl(ars'l) iso(thio)cyanates giving carbamates as a result of insertion of RNCX into the C--C bond. The kinetics and mechanism of inserhon of a~'l isocyanates into the C--C bond of the phosphonium zwitterion obtained from triisopropylphosphine and ethyl 2-cya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…It would be interesting to know what might happen to SCHEME 2 -complex like 3, if instead of labile C H bond, the α-C atom bore loosely bound C(O)OEt group (cf. [2]). To construct such -complex, we reacted 2 with zwitterion 6.…”
Section: Resultsmentioning
confidence: 93%
“…It would be interesting to know what might happen to SCHEME 2 -complex like 3, if instead of labile C H bond, the α-C atom bore loosely bound C(O)OEt group (cf. [2]). To construct such -complex, we reacted 2 with zwitterion 6.…”
Section: Resultsmentioning
confidence: 93%
“…We have earlier described the processes of 1,3 С→N migration of the alkoxycarbonyl groups occurring during the interaction of isocyanates with the carbanions based on phosphorus containing zwitterions, 1,2 esters of phenyl cyanoacetic acid, 3 and pyridinium ylides. 4 The study of the mechanism of these transformations (Scheme 1) showed 5 that the reaction proceeds in two steps, and the introduction of the electron withdrawing substituents into the arylisocyanate ring accelerates the formation of carbamates.…”
mentioning
confidence: 99%